Microbiological Quality of Cold-smoked Herring (Clupea harengus) Roe - Hamoda, Marwa E.; Ahmed, Ali M.; Ahmed, Omaima M. (Journal of Advanced Veterinary Research, 2023)
Smoked fish roes within cold smoked herring are considered a very popular ready-to-eat food in Egypt. Therefore, the microbial quality of fish roes should be of concern. The purposes of this study were to conduct bacterial analysis and the possibility of detection of foodborne pathogens. With limited application of dry heating at 85°C for 1 and 5 minutes to improve the safety of roes. To study the biogenic amines (BA) including spermine, putrescine, cadaverine, histamine, tyramine, and spermidine in fresh, heated at 85°C for 5 min, and stored at 0°C for 6 months smoked roes. Vibrio spp. including Vibrio vulnificus, Vibrio furnissii, and Vibrio carcbariae were found in 5 samples (9.6%). One Salmonella spp. (1.9%) and one Listeria monocytogenes (1.9%), 4 Staphylococcus aureus (7.7%), and 3 Bacillus cereus (5.8%) pathogens. While Clostridium botulinum (vegetative forms) were not detected. None of the aerobic, anaerobic, or selective bacterial counts existed after heating smoked roes at 85°C for 5 minutes. The average of each BA in all samples was below 3mg/100g, which is less than the 5.0 mg/100g acceptable limit recommended by the US Food and Drug Administration. Histamine and tyramine only appeared after cold storage of roes at 0°C for 6 months. Cold smoked herring roe was low in acidity (pH: 5.92), high in moisture (68.5%), protein (61.37%), and lipid content (28.7%), thus it could support the bacteria growth. Additional measures are needed to reduce the possible health risks for fish roe consumers.